Mirror therapy and self-care autonomy after stroke: an intervention program - Castro, Pedro (2019)
Background: In patients with middle cerebral artery (MCA) stroke, changes in upper limb function lead to dependence on others for self-care. In the process of recovering autonomy/independence, there is evidence on the effectiveness of sensory stimulation techniques in the motor recovery after stroke. Objective: To assess the effect of mirror therapy on the self-care autonomy of patients with hemiplegia/hemiparesis due to MCA stroke. Methodology: Cross-sectional and quasi-experimental study with a quantitative approach, a before-and-after design, and a non-equivalent control group. A nonprobability sample of 30 participants was selected. Results: Gains in grip strength, joint range of motion, and manual dexterity of the upper limb were more significant in the experimental group but without statistically significant differences between groups. Conclusion: Despite the more significant evolution of the experimental group, mirror therapy was not effective in the motor recovery of the upper limb. Further studies are needed in this area using randomized designs, larger samples, and focused on self-care.